Risk Factors for Surgical Site Infection after Hip Arthroplasty: A Multicentric Study - Tofani, Gabriel B.; Irffi, Gustavo P.; Silva, Lucas F.; da Silva, Cynthia C. M.; Couto, Bráulio R. G. M.; Miranda, Gilberto D.; Starling, Carlos E. F. (Scientific Research, 2016)
The objective of this study is to answer three main questions: What is the risk of wound infection for patients undergoing hip arthroplasty? What are the main etiologicagents of surgical site infection (SSI)? What are the risk factors most associated with surgical site infection? Method: This was a multicentric, retrospective cohort study which analyzed data collected in five general hospitals in Belo Horizonte, Brazil, between the period of January 2009 and December 2013. The continuous parameters studied were age, length of hospital stay before surgery, duration of surgery, number of professionals at surgery and number of hospital admissions. Categorical variables were surgical wound classification (clean, clean contaminated, contaminated, dirty/infected), American Society of Anesthesiologists (ASA) score (I, II, III, IV, V), type of surgery (elective, emergency), general anesthesia (yes, no), prophylactic antibiotic (yes, no), trauma surgery (yes, no) and Nosocomial Infections Surveillance (NNIS) risk index (IRIC = 0, 1, 2, 3). Results: Estimated SSI risk was 3.2% (95% C.I. = 2.6% to 4.1%) and risk of osteomyelitis was 0.6% (95% C.I. = 0.4% to 1.1%). ASA score > 2, general anesthesia, length of hospital stay before surgery higher than four days, more than two professionals at surgical field and duration of surgery higher than five hours were risk factors for SSI after hip prosthesis (p < 0.05). The final multiple logistic regression analysis indicated that the modified NNIS risk was independently associated with surgical site infection after arthroplasty of hip. Conclusion: Despite the modified NNIS index being a risk factor for SSI, none of its independent variables was statistically significantly in the logistic model (p > 0.100). Each modified NNIS risk category increased the chance of a patient being infected by almost three times, when compared with the previous category (OR = 2.82; p = 0.011).
Keywords: Surgical Site Infection; Hip Arthroplasty; Hip Replacement; Risk Factors